EFFECT OF STEEL FIBERS ADDITION ON THE BEHAVIOR OF HIGH STRENGTH CONCRETE CIRCULAR SHORT COLUMNS - Yasir M. W. Al-Shamma; Riyadh Jawad Aziz; Zubidah Abdullateef Al-Bayati (Journal of Engineering, 2011)
loaded reinforced concrete circular short columns. An experimental investigation into the behavior of 24 short reinforced concrete columns with and without steel fibers was carried out. The columns had a circular section (200 mm diameter and 900 mm long). Test variables include concrete strength, spacing of spiral reinforcement, and inclusion of steel fibers. The axial stress and axial strains were obtained and used to evaluate the effects of the presence of steel fibers. It was found that the addition of steel fibers slightly improves the load carrying capacity of the tested columns whereas it significantly enhances the ductility of these specimens. Test results also indicated that for the same confinement parameter , specimens with steel fibers has higher strength enhancement compared to specimens without steel fibers. For confinement parameter of 0.1 the strength enhancement equal 1.7 for specimens with fibers while it is 1.4 for nonfibrous specimens. An empirical expression is proposed and used to predict the confined strength of columns. It was shown that the proposed formula predicts the load carrying capacity of the tested columns reasonably.